Analysis of the Impact of Halal Certification on the Increase in Sales and Development of MSME (Case Study of UD. Mushroom Partners) - Yusril Imam Malik; imam malik, yusril; Dhofir Catur Bashori (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
This research aims to determine the impact of halal certification on sales increase and This research aims to determine the impact of halal certification on sales increases and business development in the MSME UD. Mitra Jamur Jember. This study uses a qualitative method with a descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation with the owners and employees. The results of the study indicate that holding halal certification has a positive impact on consumer trust, which subsequently significantly increases sales turnover. In addition, halal certification encourages business development in terms of product quality, production systems, and market expansion. These findings prove that halal certification is not only a form of compliance with Islamic law but also an effective business strategy to enhance the competitiveness of MSMEs.